Analysis of confounders of the image quality of a high-resolution isotropic three-dimensional Dixon water-fat late gadolinium enhancement technique - Johanna Kuhnt; Edyta Blaszczyk; Leo Dyke Krüger; Leonhard Grassow; Claudia Prieto; René Botnar; Karl Philipp Kunze; Michaela Schmidt; Darian Steven Viezzer; Thomas Hadler; Maxmilian Fenski; Jeanette Schulz-Menger (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Three-dimensional (3D) water-fat separated late gadolinium enhancement (LGE) imaging is a cardiovascular magnetic resonance imaging technique allowing simultaneous assessment of and discrimination between cardiac fibrosis and myocardial fatty infiltration. The aim of this study is to systematically analyze the image quality of a 3D water-fat separated LGE research sequence and identify confounders of image quality Methods: In total, 126 patients and 12 healthy volunteers were included. Patients were included with inflammatory bowel disease (n=35), muscular dystrophy (n=38), hypertrophic cardiomyopathy (n=23) and paroxysmal atrial fibrillation (n=30). 3D water-fat separated LGE images were acquired at 1.5T (n=122) or 3T (n=16). Image quality was subjectively rated (4-point Likert scale) in six categories (overall image quality [OV], blood-myocardium border sharpness, LGE-remote/healthy myocardium border sharpness, fat suppression, myocardial nulling [MN], anatomical structures [AS]), additionally, the contrast ratio was calculated. Cardiac function, acquisition conditions, and demographic data were investigated as potential confounders for image quality and contrast ratio. Results: Fat suppression had the highest quality score (2.54±0.72), followed by AS (2.11±0.94) and MN (2.01±0.78). In total, 18 parameters showed a significant correlation with multiple image quality categories, most of which related to cardiac function, such as the cardiac index, which significantly correlated with OV (Wald Chi-squared=4.35; p<0.05), LGE-remote/healthy myocardium border sharpness (Wald Chi-squared=5.03; p<0.05), and AS (Wald Chi-square=16.00; p<0.001). Left ventricular mass index to height showed significant correlation with OV (Wald Chi-squared=7.57; p<0.01), blood-myocardium border sharpness (Wald Chi-squared=7.35; p<0.01), and contrast ratio (Wald Chi-squared=5.50; p<0.05). Furthermore, demographic parameters, such as body mass index (BMI), were identified as significant confounders, showing a notable correlation between BMI and the depiction of AS. (Wald Chi-square=11.14; p<0.01). Conclusion: In this study, 3D water-fat separated LGE imaging shows satifactory image quality, especially for water-fat separation. However, image quality may be affected by several other parameters such as patient obesity, high myocardial mass, and cardiac function. Trial Registration: 3000339